T.QAYÍPBERGENOVTÍŃ SHÍǴARMALARÍNDA QOLLANÍLǴAN BAǴÍNÍŃQÍLÍ QOSPA GÁPTIŃ SEMANTIKALÍQ TÚRLERI - Seydullaeva, D.; Dauletmuratova, X. (SCIENCE and SOCIETY, 2024)
In the article, we studied the complex sentences with subordinate clauses in T. Kayipbergenov’s works based on the functional-semantic principle.